PENILAIAN KINERJA PERUSAHAAN MEBEL DARI PERPSPEKTIF KARYAWAN DENGAN MENGGUNAKAN METODE AHP DAN OMAX - Sri Widiyawati (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2016)
Increasingly rapid technological development has resulted in the current business competition is getting tougher. With the increased competition, the company should be able to apply the right strategy at all levels in order to meet the wishes of stakeholders. As an organization that is oriented to profit (profit oriented), during this performance measure based solely on the financial aspects of using profitability ratios. Besides measured by profit, the company's success in improving the company's performance is highly dependent on the quality of Human Resources (HR). The company's performance appraisal conducted using Analytical Hierarchy Process (AHP) that can help decision-making within the company relating to the employee. To make an assessment based on ranking or score will be used method Objective Matrix (OMAX). Scoring system based on the calculation that the data obtained are 4 KPI that fall into the red category. Among them is the KPI-2 (an increase in welfare), KPI-5 (level of discipline employees, KPI-6 (degree of achievement of employee productivity, and KPI-7 (rate of sick employees). There is also a 6 KPIs included in the yellow category. from the results of the scoring system showed that during the company's performance can not be achieved with good when viewed from the perspective of employees for only six KPIs are included in the green category and 10 KPIs others included in the category of critical KPI / needs improvement. Keywords company's performance appraisal, employee perspective, Analytical Hierarchy Process (AHP),OMAX.